Rhinophyma: a surgical treatment option - Inara do Carmo Lucchese; Daniel Ongaratto Barazzetti; Diego Fernando Villagra Avila; Gustavo Palmeiro Walter; Arthur Koerich D'Avila (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Rhinophyma is a condition involving chronic inflammation of the nose and is characterized by progressive hypertrophy and hyperplasia of sebaceous glands and connective tissue. Rhinophyma leads to an appearance of nasal elephantiasis, which is caused by the congestion of dermis vessels. Its etiology is mostly associated with alcohol abuse. Rhinophyma is considered by some researchers to be an advanced stage of acne rosacea. Here, we report a case of rhinophyma that was surgically treated with decortication and electrocoagulation at the Plastic Surgery Service of the University Hospital of the Federal University of Santa Catarina. METHODS: A review of medical and photographic records of a case of rhinophyma was conducted. RESULTS: The patient was underwent surgical treatment with favorable outcomes. CONCLUSION: There are several treatments for rhinophyma, with decortication and electrocoagulation being an excellent therapeutic option.